Britain's orchids : a field guide to the orchids of Great Britain and Ireland - Cole, Sean; Waller, Michael (WildGuides., 2020)
An accessible, comprehensive and beautifully illustrated guide--the only one to cover all the orchids found in Britain and IrelandCovering more than fifty species as well as hybrids and variants, this is an engaging, intuitive and in-depth identification guide to all the orchids of Britain and Ireland at all stages of development, from first emergence through to setting seed. Drawing on the authors' extensive field experience and the latest scientific research, Britain's Orchids uses multiple techniques to help both beginner and more advanced orchid enthusiasts to identify even the trickiest plants. The book is beautifully illustrated with plates by talented artist Sarah Stribbling as well as more than 1,000 detailed, instructive and evocative photographs by the authors. Orchids have long fired the imagination with their beauty and rarity. This book aims to ignite or increase your passion for these special plants and for the conservation of their habitats, from remote mountaintops to urban wild spaces. The first book to cover all the species, subspecies and varieties, as well as hybrids, at all stages of developmentLavishly illustrated with close to 100 stunning plates drawn to scale to show key identification features and more than 1,000 stunning photo showing orchids in their natural settingsSimple, step-by-step system for identifying almost any orchidUp-to-date distribution maps and seasonal charts showing when each species can be seen in its various stagesSpecial-feature identification keys that can be used on difficult plants.